Respons Ayam Kampung terhadap Penambahan Kalsium Asal Siput (Lymnae Sp) dan Kerang (Corbiculla molktiana) pada Kondisi Ransum Miskin Fosfor - . Khalil (Faculty of Animal Science, Bogor Agricultural University, 2006)
The objectives of this present investigation were to evaluate effects of using shell of freshwater snail as major source of calcium in the diets on performance and bone mineralization of growing native chicks (1-12 weeks of age). There were four dietary treatments. The first was a basal diet (negative control) containing 0.5 % bone meal, but deficient in phosphor. Three other diets which were relatively the same in composition as that of basal diet, but one supplemented with 2.5 % oyster shell (positive control) and two with 2.5% shell of freshwater snail obtained from two different water bodies: lake and rice field, respectively. One hundred birds of native chicken were divided into four groups of treatments with five replicates with 5 birds each and offered experimental diets for 12 weeks. Parameters measured included: body weight gain, feed intake, feed conversion ratio (FCR), weight of tibia bone and their ash and mineral (Ca and P) composition and retention. The chicks fed on diets containing shell of freshwater snails showed no significantly difference in body weight gain, feed intake and FCR with those fed on diet containing oyster shell, but significantly lower body weight gain than those fed on basal diet containing only bone meal. Feeding of diets supplemented with shell of snails and oyster decreased significantly the body weight gain. However, no significantly difference was observed in the weight and content of ash, Ca and P of tibia bone. Key words : freshwater snail, native chicken, mineral nutrition, bone mineralization